2013
DOI: 10.1097/igc.0b013e31829d2d51
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Hypoxia-Induced Factor Signaling Pathway Due to Mammalian Target of Rapamycin (mTOR) Suppression in Ovarian Clear Cell Adenocarcinoma: In Vivo and in Vitro Explorations for Clinical Trial

Abstract: Treatment by mTOR inhibitor is expected to down-regulate the cell proliferation of the CCA as a new therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Anticancer drugs targeting mTOR include everolimus, an mTOR inhibitor used to treat renal cell carcinoma (88). Gene analysis of ovarian cancer tissues revealed mTOR mutations, therefore suggesting the effectiveness of mTOR inhibitors in ovarian cancer (88)(89)(90). In mice with subcutaneously implanted human ovarian clear cell carcinoma cells, the tumor size was halved following treatment with everolimus, Taxol ® and cisplatin (86).…”
Section: Clinical Application Of the Results From Genomic Analysismentioning
confidence: 99%
“…Anticancer drugs targeting mTOR include everolimus, an mTOR inhibitor used to treat renal cell carcinoma (88). Gene analysis of ovarian cancer tissues revealed mTOR mutations, therefore suggesting the effectiveness of mTOR inhibitors in ovarian cancer (88)(89)(90). In mice with subcutaneously implanted human ovarian clear cell carcinoma cells, the tumor size was halved following treatment with everolimus, Taxol ® and cisplatin (86).…”
Section: Clinical Application Of the Results From Genomic Analysismentioning
confidence: 99%
“…Furthermore, Hirasawa et al compared four groups receiving placebo, everolimus alone, paclitaxel/cisplatin alone, and everolimus + paclitaxel/cisplatin in vivo and reported that antitumor efficacy was highest in the everolimus + paclitaxel/cisplatin group. While tumor growth was inhibited in the group receiving everolimus alone in their report, little cytoreductive effect was obtained 18. Therefore, it may be difficult to obtain an antitumor effect in ovarian clear cell adenocarcinoma with everolimus alone, and we anticipate that an additional effect would be obtained by combining this agent with other anticancer drugs.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, by relieving CIP2A inhibition of PP2A, the PI3K inhibitors would enforce PP2A action in de-phosphorylating target residues on STAT5 thereby resulting in reduced activation. The changes in CIP2A levels in cells exposed to PI3K/mTOR inhibitors were under the control of a microcircuit involving Hif1α [ 55 , 56 ] and its target SNAI1 [ 57 ], and caused enhanced expression of miR-375, a known negative regulator of CIP2A transcription. A schematic representation of this pathway, on the basis of information derived from the literature and original data from this work, is illustrated in Figure 7 .…”
Section: Discussionmentioning
confidence: 99%